1994
DOI: 10.1063/1.466316
|View full text |Cite
|
Sign up to set email alerts
|

The HeH2 energy surface

Abstract: A composite ab initio energy surface is obtained for the HeH2 triatomic molecular system by combining earlier calculations that covered parts of the surface. The extended surface covers the full angular range of He relative to the H–H axis as well as the full range of He–H2 separations. As with all calculations thus far, the extended ab initio energy surface covers only a narrow range of H–H separations in the vicinity of 1.4 a.u., the equilibrium separation of ground state H2. In addition, a new parametric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 24 publications
8
104
0
Order By: Relevance
“…The potential energy surface (PES) adopted here was that of Muchnick and Russek (MR) [23]; this surface, along with that of Boothroyd et al (BMP) [24], was discussed previously by Lee et al [25] who performed state-to-state rovibrational scattering calculations for He-H 2 and found that the MR surface gave the best agreement with available experimental data at thermal energies.…”
Section: Methodsmentioning
confidence: 88%
“…The potential energy surface (PES) adopted here was that of Muchnick and Russek (MR) [23]; this surface, along with that of Boothroyd et al (BMP) [24], was discussed previously by Lee et al [25] who performed state-to-state rovibrational scattering calculations for He-H 2 and found that the MR surface gave the best agreement with available experimental data at thermal energies.…”
Section: Methodsmentioning
confidence: 88%
“…Figures (16) and (17) display the quasiresonance domain associated with the nonlinear resonance N : M = 1 : 1 for different number m of coupling terms. As was expected, the resonance zone presents a chain composed of mM islands, two in figure (16) and three in figure (17), associated with the mM elliptic and mM hyperbolic fixed points located at the resonance action J 1:1 2,E . The thick lines on the Poincare surface of sections represent the curves of the separatrices Υ N :M k (τ p , φ 1 ) (k = 1, ...m) (61) when the transient interaction reachs its maximum amplitude at τ = τ p .…”
Section: Span Of a Quasiresonance Domainmentioning
confidence: 83%
“…We obtained the diatomic vibrational wave functions used in generating the coupled equations as expansions in Hermite polynomials with the diatomic H 2 potential of [17]. Close-coupling calculations for collisions of 4 He with H 2 have been carried out using various potential energy surfaces and scattering formulations [18][19][20][21][22], and rate coefficients have been reported for temperatures above 50 K. We have adopted the more recent potential energy surface (PES) of Muchnick and Russek [23]. In Fig.…”
Section: Quenching Of H 2 Vibrations In Ultracoldmentioning
confidence: 99%